The response of bullwhip effect to grey and fuzzy grey GM(1,1) forecasting models - (:unkn) unknown (World Scientific Publishing Co. Pte Ltd, 2008)
One of the pernicious master issues of supply chain is the bullwhip or whiplash effect; i.e. the variability of the demand information between stages of the supply chain and the increase of this variability as the information moves upstream through the chain. In this paper, the reaction of bullwhip effect to grey and fuzzy grey GM(11) forecasting models is analyzed by quantifying the bullwhip effect with variance estimation and Lyapunov exponent using a simple supply chain Matlab simulation (i.e. beer game model) and results derived from the simulation compared with the ones obtained from using selected crisp forecasting model.
Keywords: Bullwhip effect; Exponential smoothing; Forecasting; Fuzzy grey GM (1, 1) model; Grey GM (1, 1) model; Lyapunov exponent; Supply chain